An investigation into using rammed stone columns for the improvement of a South African silty clay - Sobhee-Beetul, Laxmee (Department of Civil Engineering, 2016)
Ground improvement is the term used to describe the act of modifying the soil properties in geotechnical engineering. It is often required when the existing ground conditions do not meet the requirements for a construction project. The technique of improving the ground are many and they usually aim at reducing settlement, increasing bearing capacity, mitigating liquefaction, improving drainage, retaining unstable soils or remediating contaminated soils. Among these techniques, stone column technology which was pioneered in the 1950s' aimed at improving both cohesive soils and silty sands. Although the technique has been used successfully in many advanced countries, its application in South Africa is minimal. This limited use is associated with a lack of research, instrumented case studies and design specifications pertaining to local ground conditions. In this investigation, the behaviour of rammed stone columns installed in a South African clay (sourced from District Six in Cape Town) was studied through extensive laboratory tests conducted in a specifically designed rectangular wooden tank. A testing programme was established whereby the majority of the tests were conducted on the local clay, with a few performed on Kaolin for comparison purposes. The effect of moisture content (OMC, LL and 1.2LL) of the base soil specimen, the column diameter (50 mm, 70 mm and 100 mm) and the column material (Klipheuwel sand, Cape Flats sand and crushed aggregate) on the normal compressive stress applied up to a settlement of 50 mm were studied. The vertical stresses and settlements were recorded electronically and analysed. Results indicated an increase in vertical applied stress with a simultaneous reduction in settlement when improving Cape Town clay with rammed stone columns. The in-depth analysis showed that the vertical bearing stresses were generally higher with larger columns, irrespective of the column material and the moisture content of the base soil. Furthermore, 100 mm diameter crushed aggregate columns repeatedly exhibited higher improvement compared to identical columns made out of sand. Nevertheless, for smaller columns the coarser sand (Klipheuwel) performed better than all three column materials. In general, columns failed in bulging with the maximum bulge occurring within the top third of the column. This study deepened the understanding of the performance of rammed stone columns in fine grained soils. The results obtained recommended full scale investigations with a view of applying the technology in slope stability, strip footing foundations and supporting lightweight structures.